2009
DOI: 10.1039/b819791a
|View full text |Cite
|
Sign up to set email alerts
|

Au nanoparticles on a templating TiOx/Pt(111) ultrathin polar film: a photoemission and photoelectron diffraction study

Abstract: We present an in-depth investigation of Au nanoparticles self-assembled on a zigzag-like TiO(x)/Pt(111) ultrathin polar film, whose structure is known in great detail. The peculiar pattern of defects (picoholes) templates a linear array of size-selected (ca. 1 nm) Au nanoparticles without disruption of the titania layer, as observed by scanning tunneling microscopy. Their structure and electronic properties have been investigated by several large-area spectroscopic tools, i.e. high-resolution core and valence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…[12][13][14] In contrast, scanning tunneling microscopy (STM) studies of Pd on FeO/Pt(111) showed the wetting behavior of the metal, because of its strong interaction with the substrate. [12][13][14] In contrast, scanning tunneling microscopy (STM) studies of Pd on FeO/Pt(111) showed the wetting behavior of the metal, because of its strong interaction with the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In contrast, scanning tunneling microscopy (STM) studies of Pd on FeO/Pt(111) showed the wetting behavior of the metal, because of its strong interaction with the substrate. [12][13][14] In contrast, scanning tunneling microscopy (STM) studies of Pd on FeO/Pt(111) showed the wetting behavior of the metal, because of its strong interaction with the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…These play an active role as preferential nucleation sites for the growth of metal NPs (see below). 17,18 For the w 0 -TiO x film, having a stoichiometry close to that of the z 0 -TiO x phase, 22 the STM data do not show any evidence of ordered arrays of defects. 32 In the fully stoichiometric rect 0 -TiO 2 phase, 24 a Pt-O-Ti interface is formed, and, as a consequence of the weaker Pt-O interaction with respect to the Pt-Ti one, 33 a partial dewetting of the film occurs which drives the system toward the formation of flat and regularly shaped rect 0 -TiO 2 islands (with a minimum thickness of two bilayers), which progressively increase their lateral size and thickness as a function of the Ti coverage.…”
Section: Resultsmentioning
confidence: 96%
“…When an ordered array of point defects is present on the UT film, it can act as a template for a directed assembling process, eventually providing an ordered array of NPs. [10][11][12][13][14][15][16][17][18][19] However, the extrapolation of the properties obtained on such UHV model catalysts to realistic catalytic conditions is an operation which is not necessarily legitimate, and studies checking the validity over the so-called material and pressure gaps are certainly needed. 20 In recent years, some of us focused the attention on UT TiO x films deposited on a Pt(111) single crystal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations